Nanoparticle-Mediated T-Cell Drug Delivery: A Synergistic Approach for Enhanced Cancer Therapy - Sathiyabama R,; H. Gayathri,; N. Damodharan, (The Bioscan, 2025)
Worldwide, cancer is a major cause of death, and solid tumors represent unique challenges for treatment success. Although T-cell-based immunotherapies have enjoyed some success in hematological malignancies with CAR T cells and T-cell receptor-engineered therapies, they have limited efficacy against solid tumors because of poor tumor infiltration, immunosuppressive tumor microenvironments (TME), and antigen heterogeneity. Nanomedicine provides an excellent opportunity to overcome these barriers by enhancing T-cell functionality and achieving targeted delivery of drugs. With controlled release, this type of drug delivery system provides an improved pharmacokinetic profile with selective tumor-targeted delivery while minimizing systemic toxicity. In addition, T-cell-conjugated nanoparticles can enhance immune cell infiltration, modulate TME, and improve the persistence and activity of adoptive T-cell therapies. Therefore, this review focuses on the recent advances of T-cell drug delivery by nanoparticles to optimize T-cell therapy by enhancing tumor penetration and relieving immune suppression while increasing therapeutic efficacy. A special focus is also given to their applications in treating CNS tumors, where standard therapy faces added challenges instituted by the blood-brain barrier. This would reciprocally present an opportunity to synergize nanotherapy-T-cell therapy combinations toward improving therapeutic gains in solid tumors while expanding the applicability of immunotherapy in oncology.